O dispositivo equipe em Saúde Mental na Atenção Básica à Saude: um fazer entre profissões - Ribeiro, Sérgio Luiz (2016)
It is a study of the team apparatus in the primary health care services in their mental health activities and the work a between professions, understood as fundamental mechanisms for Psychiatric Reform from the perspective of Psychosocial Attention. The specific objectives were: 1) systemize the debate on the process of working as a team in the field of Psychiatric Reform; 2) identify and analyze the operation and dimensions of groupality and between professions in accompanied health team. The work was organized in two parts. The first dealt about the historical emergence of the team apparatus from the contributions of Psychiatric Reform in Europe around the work process. In this part we also present the concepts produced by brazilians professionals and researchers on the team work in the health field: Field and Core Competence and Responsibility, Common Clinic and the Between-professions, that were combined with the concept device, our analysis tools. The second part of this work was the realization of an intervention-research in a view to French Institutional Analysis, in a Basic Health Unit - the Mental Health Center, wat do the mental health care in a small town in the São Paulo State. This consisted in the accompaniment the activities of this service and realization four thematic meetings with the team about their work process. This service work it as a hybrid, performing, at the same time, practice as Basic Health Unit and how Mental Health Ambulatory and others who approach the work of a Psychosocial Care Center. Such hybrid arrangement suggests that there is this experience powers to forge under a small municipality the singularity of mental health care. In their work process this team operates professional borders and tensions in building one between-common, with the understanding that the multiplicity is an engine of this production, and at the same time, which is fundamental respect for differences of opinions and practices in daily. Is important that the health services, in addition to organizational activities, create possibilities for joint performances and encounters of professionals that weave the reflection of between-professions and do the common in team. The professionals of Mental Health Center have been challenged to exercise the protagonist in building a care mental health network in the city. But have faced doubt take on this role, the difficulties of short supply of services, equipment and programs, preconception and a medicalized view of psychic suffering present in this territory. In this context, we consider it necessary to discuss other financing possibilities and types of mental health services, which can take effect in small cities, the most in Brazil, according to your needs and possibilities